Productivity and Cost Efficiency of Commercial Banks in India - Narayanaswamy, T.; Muthulakshmi, A. P. (Indian Journal of Finance, 2016)
This paper examined the productivity and relative cost efficiency of all commercial banks in India from 1993 to 2013 using the data envelopment analysis methodology and Malmquist index. The percentage of banks in the bank groups, such as foreign banks (69%), nationalized banks (58%), and old private sectors (77%) that experienced technological change were considerably higher than the new private sector banks and State Bank of India (SBI) associate banks. The total factor productivity changes of the aforementioned three bank groups was due to technological rather than technical efficiency change. Percentage of cost efficient banks in the bank groups such as the new private sector group (75%), SBI and Associate banks (67%), and old private sector banks (56%) was considerably higher than foreign and nationalized banks. The correlation between cost efficiency and technical efficiency ranged from 0.629 to 1 (moderate to strong positive) for different groups of banks. The correlation between cost efficiency and total factor productivity change ranged from -0.067 to -0.993 (weak to strong negative) for different groups of banks.